Microtus xanthognathus - James H. Honacki; Kenneth E. Kinman; James W. Koeppl (Alien Press, Inc. & The Association of Systematics Collections, 1982)
Microtus xanthognathus (Leach, 1815). Zool. Misc., 1:60. REVIEWED BY: R. E. Barry, Jr. (REB). TYPE LOCALITY: Canada, Manitoba, Ft. Churchill?, "Hudson Bay." DISTRIBUTION: C. coast of Hudson Bay in Manitoba (Canada) to C. Alaska (U.S.A.) and N.E. British Columbia (Canada). COMMENT: Subgenus Microtus; see Anderson, 1959, Univ. Kans. Publ. Mus. Nat. Hist., 9:415-511. Anderson, 1960, Univ. Kans. Publ. Mus. Nat. Hist., 12: 192, suggested that this species may be most closely related to chrotorrhinus; dental characters indicate specific distinctness (SRL), as do size differences (REB); see also Guilday et al., 1978, Bull. Carnegie Mus. Nat. Hist., 11: 1 -67. ISIS NUMBER: 5301410008080047001. Published as part of James H. Honacki, Kenneth E. Kinman & James W. Koeppl, 1982, Order Rodentia (Part 4), pp. 477-504 in Mammal Species of the World (1 st Edition), Lawrence, Kansas, USA :Alien Press, Inc. & The Association of Systematics Collections on page 498, DOI: 10.5281/zenodo.7353034